(untitled) (Revista Sistemas de Producción Agroecológicos, 2021)
The objective of this research work was to disseminate the advances in techniques for agricultural production that are relevant for the Colombian Orinoquia, as well as to inform about trends in technology and lifestyles. Thus be able to contribute to the development of the rural communities in the region through the podcast ’’ Espacio Rural ’’, using mass communication methods such as Spotify, Ivoox, and YouTube. The project began in 2020 in the department of Meta, and was classified as a qualitative research process using the participation of the target population as a method. For this, three stages were considered, which are the pre-production, production, and post-production stage. Additionally, a survey was conducted with 137 agricultural producers in the region, which sought to inquire about the topics of most significant interest, as well as easily accessible channels to get to the information that was addressed in each program. 70.1% of the people surveyed considered that updating on agricultural issues is very important because most people are involved in the sector. 33.6% indicated that the topic of interest in the sector is the production of large species, followed by 29.9% who showed interest in issues associated with minor species, and 94.9% indicated that they are willing to listen to a podcast on these issues. The use of the podcast as an instrument for disseminating information is a valuable tool to help rural extension processes. Agricultural producers in the region consider it very important to be informed about agricultural issues and are willing to listen to podcasts through digital platforms; however, some still prefer traditional media. Therefore, it is necessary to interrelate digital platforms with traditional channels to have greater coverage of the information towards the population.